Effect of temperature on seed germination of ornamental herbaceous perennials - Pivetta, K. F L [UNESP]; Pizetta, P. U C [UNESP]; Pimenta, R. S. [UNESP]; Da Luz, P. B. [UNESP]; Coan, R. M. [UNESP]; Batista, G. S. [UNESP] (My University, 2013)
Antirrhinum majus L. and Senecio douglasii DC. are herbaceous perennial ornamental plants used in landscaping. The multiplication of these plants is by seed; however, there are still doubts about the temperature that can provide higher rates and speed of germination. Thus the aim was to study the effect of temperature on seed germination of A. majus and S. douglasii. The study was conducted separately for each species. The experimental design was entirely randomized with six temperature conditions (temperature controlled constant of 20, 25, 30, 35°C and alternating temperatures of 20-30 and 25-35°C with a photoperiod of 12 hours) with four replications of 100 seeds each. Total germination percentage and germination rate were determined. The means were compared by Tukey test at 5%. For A majus the highest germination percentage was observed at 20°C that did not differ statistically from other temperatures. The highest germination rate was obtained at the temperature of 20 and 25°C. For S. douglasii seeds it was observed that the highest germination percentage and germination rate occurred at 20°C. The lower temperature showed the better percentage and germination rate for these species.
Keywords: Antirrhinum majus; Germination; Senecio douglasii; Sexual propagation